P-084 Vitamin D Deficiency in Asian IBD Patients: Prevalence and Effect of Vitamin D Supplementation on Disease Activity and Health-Related Quality-of-Life. (March 2016) - Ong, Wan Chee; Wan, Choon Nam; Ho, Choon Siang; Valerie Ng, Yun Ting; Lim, Teong Guan; Webber Chan, Pak-Wo; Kong, San Choon; Ling, Khoon Lin; Ong, Pei Shi
Abstract : Background: Inflammatory bowel disease (IBD) are chronic inflammatory disorder of the gastrointestinal tract with unclear etiology. Increasing body of literature supports the immune-modulatory properties of vitamin D (VitD) and its involvement in the pathogenesis of IBD. At present, little is known about the VitD status of Singaporean adult IBD patients. It is also unclear how VitD supplementation can modify IBD disease activity. Hence, the study aims to (1) determine the prevalence of VitD deficiency and insufficiency in local IBD patients, (2) identify demographic and clinical variables that affect baseline serum 25(OH)D levels and (3) explore efficacy and safety of oral 3000IU/day VitD3 supplementation in VitD deficient or insufficient IBD patients. Methods: A prospective study was conducted at Singapore General Hospital Outpatient IBD Centre from July 2014 to July 2015. Serum 25(OH)D concentration was measured using radioimmunoassay. VitD deficiency and insufficiency were defined according to the Endocrine Society Guidelines. Eligible IBD patients identified to be VitD deficient or insufficient were started on 3000 IU/d of cholecalciferol (VitD3). Short IBD Questionnaire-(sIBDQ), Harvey Bradshaw Index (HBI) and partial Mayo Index were used to evaluate patient's quality of life (HQOL) and disease activity pre and post-supplementation. Prevalence of VitD deficiency and insufficiency was computed and expressed as percentage. The distribution of serum 25(OH)D in the study was markedly skewed towards lower values. Thus, non-parametric statistical tests were used. Multiple linear regression modeling was performed on logarithmically transformed values to define variables that significantly affected baseline serum 25(OH)D levels. Serum 25(OH)D levels, disease activity and sIBDQ at baseline and 6-months post-supplementation were evaluated using Wilcoxon sign rank test. Results: One hundred patients were screened. Among them, 44% had VitD deficiency and 47% had VitD insufficiency. Median serum 25(OH)D level was 21.1 ng/mL, significantly lower in UC than CD patients (19.3 ng/mL versus 23.2 ng/mL, P = 0.012). Multiple linear regression identified age ( P = 0.031), use of other VitD-containing supplements ( P < 0.001) and baseline albumin concentration ( P = 0.011) to be significant positive factors associated with log-transformed 25(OH)D levels, whereas a diagnosis of UC ( P = 0.009) was associated with lower log-transformed 25(OH)D levels. Twenty-eight patients gave consent for initiation with cholecalciferol with 16 patients (6 CD; 10 UC) completing 6-months of VitD3 supplementation. Oral VitD3 supplementation significantly increased median 25(OH)D level from 18.1 ng/mL to 38.4 ng/mL ( P < 0.05). CD patients had an improvement in sIBDQ score only (+8.5 points; P = 0.068) whereas UC patients showed an improvement in both partial Mayo index score (−1.5 points; P = 0.131) and sIBDQ (+3.5 points; P = 0.058). However, concurrent medication changes might have affected disease control. Serum calcium and phosphate were within normal range at the start and end of study. Conclusions: High proportion of IBD patients had VitD deficiency and insufficiency. Regular screening is recommended. Special attention should be paid to younger UC patients with low albumin concentrations and not taking any VitD supplements. Oral VitD3 3000IU supplementation effectively raised serum 25(OH)D levels and showed improvement in HQOL. However, its effect on disease control remained inconclusive. Doses of VitD3 supplementation should be tailored to at least 3000 IU/day to achieve 40 ng/mL for immune-modulating effect.